2020
DOI: 10.1016/j.cmi.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Development of new methods for detecting bloodstream pathogens

Abstract: Background: Current blood culture systems were developed and evolved, in part, based on our knowledge of the critical factors in the recovery of pathogenic microorganisms from blood, changes in the spectrum of pathogens causing bloodstream infections, changes in technology and changes in expectations for blood culture system performance. Aims: The aim was to review historical data about development of blood culture systems and how that knowledge will continue to influence newer generations of technology for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Especially the identification of the infection-causing pathogen remains time consuming when cultivation-based microbiological methods are used. Detailed information on the infectious agent is usually only available within 24 to 48 h, but might take even longer in case of uncommon or fastidious pathogens [ 7 , 8 ]. The extended time-to-results forces the treating physician to use empirical antibiotic treatment, which is not always appropriate for eliminating the pathogen and leads to high resistance rates, especially in nosocomial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Especially the identification of the infection-causing pathogen remains time consuming when cultivation-based microbiological methods are used. Detailed information on the infectious agent is usually only available within 24 to 48 h, but might take even longer in case of uncommon or fastidious pathogens [ 7 , 8 ]. The extended time-to-results forces the treating physician to use empirical antibiotic treatment, which is not always appropriate for eliminating the pathogen and leads to high resistance rates, especially in nosocomial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the panel requires a whole-blood sample of 4 mL ( , accessed on 27 July 2021), which is consistent with that (1−5 mL) of aforementioned nucleic acid amplification-based tests—in particular the VYOO assay uses a volume of 5 mL of whole blood [ 6 ]. If the T2Bacteria ® panel or the VYOO assay should be performed in triplicate, volumes of 12−15 mL would be equivalent to the input volume for a single BC—usually at least two sets of BCs per patient are drawn at the time of BSI [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid identification of the causative pathogen allows time to diagnosis and targeted therapy of BSI/sepsis to be considerably shortened [ 6 ]. Since blood culture (BC) remains the reference standard in BSI diagnostics [ 7 ], positive BC testing in the clinical microbiology laboratory has embraced new panel-based molecular assays [ 8 ]. In addition to identifying the most common pathogens isolated from BCs (e.g., Enterobacterales ) within few hours, these assays can detect antimicrobial resistance determinants, such as the Klebsiella pneumoniae carbapenemase (KPC), which is encoded by the bla KPC gene [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treating severe infections due to multidrug-resistant Gram-negative bacteria is one of the most important challenges for clinicians worldwide and the major efforts of the scientific community have been mainly focused on the development of rapid microbiological tests for BSI due to multidrug resistant Gram-negative bacteria [ 72 ]. However, it has been reported that in routine patient care S. aureus is the most common pathogen isolated from blood and, together with Enterobacterales , accounts for approximately half of all blood culture isolates in most studies [ 30 ]. Optimal patient care requires access to necessary laboratory testing including clinical microbiology, and a rethinking of hours of operation is required, i.e., 24 h/7 days a week open laboratory, to shorten time of accurate result reporting [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several molecular panels able to simultaneously detect many organisms, including MSSA/MRSA, in one sample have been developed for the diagnosis of infectious syndromes. Depending on the test used, MRSA can be detected 12–48 h earlier than with traditional methodologies [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%